Pan-genome analysis and expression verification of the maize ARF gene family - Man, Quan-cai; Wang, Yan-qun; Gao, Shun-juan; Gao, Zhi-chang; Peng, Zheng-ping; Cui, Jiang-hui (Frontiers in Plant Science, 2025)
Auxin transcription factors regulate auxin responses and play crucial roles in plant growth, development, and responses to abiotic stress. Utilizing the maize pan-genome data, this study identified 35 ARF family members in maize, comprising 21 core genes, 10 near-core genes, and 4 non-essential genes; no private genes were detected. The construction of a phylogenetic tree using Arabidopsis thaliana revealed that the G3 subfamily comprises the highest number of core genes, with a total of 10, and exhibits relative stability throughout the evolution of maize. The calculation of the Ka/Ks ratios for ARF family members across 26 genomes indicated that, aside from ARF8 and ARF11, which were subjected to positive selection, the remaining genes underwent purifying selection. Analysis of structural variation revealed that the expression level of the ARF4 gene significantly differed as a result of this variation. Simultaneously, the structural variation also influenced the conserved domain and cis-acting elements of the gene. Further combining the transcriptome data and RT-qPCR found that, The expression levels of ARF family members in maize were higher at the early stage of embryo and grain development, and the expression levels of each member in embryo and grain were complementary, and the ARF4 plays an important role in abiotic stress. In summary, this study utilizes the maize pan-genome and bioinformatics methods to investigate the evolutionary relationships and functional roles of ARF family members in maize, thereby providing a novel theoretical framework for further research on the maize ARF family.